2017
DOI: 10.31229/osf.io/v8ak9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relawan: Dari Gerakan Sosial ke Proyek Politik

Abstract: PendahuluanFenomena relawan atau volunteerisme dalam kontestasi elektoral di Indonesia menjadi kajian politik yang menarik untuk dikaji secara lebih mendalam. Kajian tentang volunteerisme juga penting untuk dilakukan. Sebab, peran relawan yang begitu besar dalam membangun basis dukungan untuk memenangkan kandidat yang diusung. Peran volunteerisme ini tidak dapat diangggap remeh di tengah krisis kepercayaan kepada partai politik yang kian kehilangan legitimasi politiknya. Volunteerisme akhirnya muncul sebagai k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Most studies regarding the phenomenon of volunteerism in the 2014 residential election have suggested a connection between the role of civil society (in the form of volunteers) and democratization in Indonesia (Sefsani and Ziegenhain 2015;Hasanuddin 2014; Suaedy 2014; Ambyo 2014; Arianto 2014) on the basis of two reasons: first, these volunteers -who worked individually and in groups, across all classes in society, had various backgrounds -emerged as a progressive civil society (Mietzner 2013) characterized by autonomous and voluntary organizations motivated by pro-democratic goals (Sefsani and Ziegenhain 2015) with a high degree of political awareness (Samah and Susanti 2014). Second, the role of volunteers is considered as a breakthrough for political change in Indonesia (Suaedy 2014) and is in line with civil society's democracy-building functions that deepen democracy in the country (Sefsani and Ziegenhain 2015;Hasanuddin 2014;Okamoto 2014) and help change the political values of patrimonial and oligarchic nuance in Indonesian political tradition (Alam, et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies regarding the phenomenon of volunteerism in the 2014 residential election have suggested a connection between the role of civil society (in the form of volunteers) and democratization in Indonesia (Sefsani and Ziegenhain 2015;Hasanuddin 2014; Suaedy 2014; Ambyo 2014; Arianto 2014) on the basis of two reasons: first, these volunteers -who worked individually and in groups, across all classes in society, had various backgrounds -emerged as a progressive civil society (Mietzner 2013) characterized by autonomous and voluntary organizations motivated by pro-democratic goals (Sefsani and Ziegenhain 2015) with a high degree of political awareness (Samah and Susanti 2014). Second, the role of volunteers is considered as a breakthrough for political change in Indonesia (Suaedy 2014) and is in line with civil society's democracy-building functions that deepen democracy in the country (Sefsani and Ziegenhain 2015;Hasanuddin 2014;Okamoto 2014) and help change the political values of patrimonial and oligarchic nuance in Indonesian political tradition (Alam, et al 2017).…”
Section: Introductionmentioning
confidence: 99%